Arbitration Reform - S. Stepurina (Правоприменение, 2017)
УДК 347.73:341.63Subject. This informational article highlights recent changes to the Russian legislation on arbitration.Purpose. To highlight the most important aspects of arbitration law reform, and examines the effects they will have on the development of arbitration in RussiaMethodology. The author uses a formal-legal method.Results, scope of application. The author distinguishes the difference between constantly acting arbitration courts and arbitration courts ad hoc). The special status of a number of arbitration institutions (the ICAC and MAC at the Russian Chamber of Commerce and Industry), is contrary to the constitutional principle of equality under the law. A major achievement of the new legislation on arbitration courts is expanding the range arbitrarily disputes.Conclusions. The new legislation more clearly prescribed the interaction of arbitration and state courts, including requiring the latter to promote the arbitrators, acting under the regulations of the permanent arbitration institutions in obtaining evidence.In addition, the reform of the arbitration law have left aside the problem of improving the quality of judicial control over arbitration decisions.The arbitration law will still be able to improve the arbitration, to enhance its credibility and attractiveness for the participants of civil turnover.